Financial technology-based management and finance integration strategy to realize organizational sustainability - Elly Yuniar Nitawati; Nurul Iman; Indah Noviandari (Nomico, 2026)
This study aims to critically analyze the strategy of integrating financial technology-based management and finance in realizing organizational sustainability. Digital system integration is often perceived as a rational solution to fragmented organizational management, but empirical practice shows that integration does not always result in substantive strategic alignment. This study uses a qualitative approach with a theoretical-analytical qualitative design to explore the dynamics of integration, the quality of decision-making, organizational governance, and their implications for sustainability. Data were collected through in-depth interviews with strategic organizational actors, non-participatory observation, and document analysis, then analyzed using thematic and conceptual approaches. The results show that financial technology-based integration can improve operational efficiency, information transparency, and decision-making speed, but also has the potential to create an illusion of integration when focused solely on technical aspects. The dominance of financial logic, decision centralization, and systemic dependency emerge as consequences that narrow strategic flexibility. From a sustainability perspective, technological integration strengthens short-term operational resilience, but does not necessarily drive long-term strategic transformation. This study emphasizes that organizational sustainability requires a reflective, participatory, and balanced integration approach between efficiency, control, and adaptability, so that technology functions as a strategic enabler, not the ultimate goal of organizational management.